Volunteers in Public Schools Adult Basic Education VIPS/ABE. Final Report / M. Margaret Welliver. - Welliver, M. Margaret (Distributed by ERIC Clearinghouse, 1983)
A project was designed to establish a model linkage between a well-established community service organization and an adult basic education (ABE) program. During 1982-83 members of the State College Kiwanis Club were recruited and trained as tutors in the State College Area School District ABE/General Educational Development (GED)/English as a Second Language (ESL) program. Support sessions were held to provide tutors and staff with opportunities for feedback, and volunteers were provided with a bibliography of resources. A handbook for volunteers was developed. Evaluation instruments were administered to students and tutors in each of the two project phases. Responses indicated success and alerted the project director to problem areas in need of improvement. Following the seven-page narrative are these appendixes: project correspondence, materials for tutor recruitment, tutors' reactions to visitation/orientation/training, training materials for staff regarding working successfully with volunteers, and results of student and tutor evaluation, including a report detailing achievement of objectives and problem areas. (YLB)
Sponsoring Agency: Pennsylvania State Dept. of Education, Harrisburg. Div. of Adult Education and Training Programs.
ERIC Note: Prepared by the Continuing Education Program.
ERIC Document Number: ED255748.
Keywords: Adult Basic Education.; Adult Programs.; Evaluation.; Program Development.; Program Implementation.; Publicity.; Recruitment.; Tutoring.; Tutors.; Volunteer Training.; Volunteers.